The ABCB7-Like Transporter PexA in Rhodobacter capsulatus Is Involved in the Translocation of Reactive Sulfur Species - Riedel, Simona; Siemiatkowska, Beata; Watanabe, Mutsumi; Müller, Christina S.; Schünemann, Volker; Hoefgen, Rainer; Leimkühler, Silke (Frontiers in Microbiology, 2019)
The mitochondrial ATP-binding cassette (ABC) transporters ABCB7 in humans, Atm1 in yeast and ATM3 in plants are highly conserved in their overall architecture and particularly in their glutathione binding pocket located within the transmembrane spanning domains. These transporters have attracted interest in the last two decades based on their proposed role in connecting the mitochondrial iron-sulfur (Fe-S) cluster assembly with its cytosolic Fe-S cluster assembly (CIA) counterpart. So far, the specific compound that is transported across the membrane remains unknown. In this report we characterized the ABCB7-like transporter Rcc02305 in Rhodobacter capsulatus, which shares 47% amino acid sequence identity to its mitochondrial counterpart. The constructed interposon mutant strain in R. capsulatus displayed increased levels of intracellular reactive oxygen species without a simultaneous accumulation of the cellular iron levels. The inhibition of endogenous glutathione biosynthesis resulted in an increase of total glutathione levels in the mutant strain. Bioinformatic analysis of the amino acid sequence motifs revealed a potential aminotransferase class-V pyridoxal-5’-phosphate (PLP) binding site that overlaps with the Walker A motif within the nucleotide binding domains of the transporter. PLP is a well characterized cofactor of L-cysteine desulfurases like IscS and NFS1 which has a role in the formation of a protein-bound persulfide group within these proteins. We therefore suggest to rename the ABCB7-like transporter Rcc02305 in R. capsulatus to PexA for PLP binding exporter. We further suggest that this ABC-transporter in R. capsulatus is involved in the formation and export of polysulfide species to the periplasm.